Emergency remote education in the state of Mato Grosso: challenges present in physical education teaching (Research, Society and Development, 2021)
The Emergencial Remote Teaching (ERT) was necessary during the COVI-19 pandemic. Thus, school, students and teachers had to get readaption about teaching and learning process. This paper aimed to analyze the teacher’s perceptions about those transformations, also to identify the main challenges faced in Physical Education Teaching. The paper’s approach was descriptive qualitative. Eleven teachers from municipal educacional staff that are Physical Education Master's Degree students were our sample. Interviews were used for data harvest and data analyses were organized by tematic axises. The main findings showed the subjects had trouble using digital technologies, and had trouble reaching the students. There were a lot of changes on the way that Education Physical classes happen, one of them, a frequent way of conceptual teaching. The changes also provided faster advances in the use of digital technologies in classes and bringing the family closer to the school environment. We believe that the ERT generated great challenges and difficulties for the school, teachers and family, as well as providing great learning that will be taken to presencial teaching when it returns.